The Effects of Hassles (Stressors) and Different Coping Styles on Tertiary Students' Mental Health - Chong, Kian Jia; Dhachayani, Sinniah; Teoh, Hsien Jin (Faculty of Psychology, Universitas Surabaya, 2007)
The purpose of this study is to look at the relationship between stressors (hassles), coping and mental health. This study also tried to analyze which factor (coping or hassle) is more important in predicting mental health. Tertiary students (N = 152) from different racial groups participated in this study. The participants filled out the General Health Questionnaire (GHQ), the Hassle scale and the Functional Dimensions of Coping Scale (FDC). Results indicated that stressfulness of hassles, ra- ther than the total number of hassles, was a better predictor of various mental health problems. In ad- dition, people who use avoidance or isolation as their coping strategy has higher mental health prob- lems. Most importantly, the coping strategy (isolation or avoidance) was more important in predicting mental health than the severity of hassles. These findings are congruent with several studies done overseas and theories postulated by other researches. Tujuan kajian ini adalah melihat hubungan antara stresor, cara mengatasi tekanan dan kese- hatan mental. Kajian ini juga menganalisis faktor yang lebih penting memprediksi kesehatan mental seseorang. Sejumlah mahasiswa (N = 152) dari berbagai kelompok etnis berpartisipasi dalam kajian ini. Para subjek mengisi borang General Health Questionnaire, The Hassle Scale dan Functional Di- mensions of Coping Scale. Hasil-hasil menunjukkan bahwa intensitas stres akibat hassles (“kesuli- tan”), dan bukan jumlah total hassles yang merupakan prediktor yang lebih baik untuk berbagai masa- lah kesehatan mental. Di samping itu, mereka yang memakai penghindaran atau isolasi sebagai stra- tegi mengatasi masalahnya memiliki masalah kesehatan mental yang lebih tinggi. Yang terpenting, strategi mengatasi masalah (isolasi atau penghindaran) lebih penting memprediksi kesehatan mental daripada parahnya perselisihan. Temuan ini selaras dengan berbagai kajian yang telah dilakukan di mancanegara dan teori yang dipostulatkan peneliti lain.